Service Quality and Customer Retention of Deposit Money Banks in North-Western Nigeria - Pere Abinabo; Jibrin Nuhu Shagari; Munir Shehu Mashi; Adamu Yahaya (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: In a financial climate that is becoming more and more dynamic, a bank's ability to retain customers is crucial to its sustainability and competitiveness. In the banking industry, it is commonly acknowledged that client happiness and long-term loyalty are mostly determined by service quality.Objectives: The goal of this study is to examine how several aspects of service quality such as empathy, dependability, responsiveness, technology, and trust affect retail banking customers' retention in commercial banks in Northwestern Nigeria.Methods: This study used a cross-sectional survey design and a quantitative methodology. A five-point Likert scale served as the primary assessment tool in a structured questionnaire used for data collection. 499 retail banking clients at specific urban branches of seven major banks provided the data. The association between customer retention and service quality aspects was evaluated, and the relative strength of each predictor was ascertained, using SmartPLS and structural equation modeling (SEM).Result: The study's conclusions show that client retention is strongly and favorably impacted by empathy, dependability, responsiveness, technology, and trust. Reliability and responsiveness were found to be the strongest predictors among these variables, indicating that accurate service delivery and timely replies are crucial for preserving customer loyalty.Conclusion: This study emphasizes the necessity for banks to invest in safe, effective, and user-friendly digital technology while bolstering the provision of dependable and responsive services. These results provide bank managers with useful recommendations for improving service tactics that sustain long-term client retention and competitive advantage.